The fictions of translation - Woodsworth, Judith; Lane-Mercier, Gillian, 1956-; Godbout, Patricia; Ruschiensky, Carmen (Benjamins translation library ;, 2018)
In 'The Fictions of Translation', emerging and seasoned scholars from a range of cultures bring fresh perspectives to bear on the age-old practice of translation. The current movement of people, knowledge and goods around the world has made intercultural communication both prevalent and indispensable. Consequently, the translator has become a more prominent figure and translation an increasingly present theme in works of literature. Embedding translation in a fictional setting and considering its most extreme forms ? pseudotranslation or self-translation, for example ? are fruitful ways of conceptualizing the act of translating and extending the boundaries of translation studies. Taken together, the various translational fictions examined in this collection yield new insights into questions of displacement, migration and hybridity, all characteristic of the modern world. 'The Fictions of Translation' will thus be of interest to practising translators, students and scholars of translation and literary studies, as well as a more general readership.